Excel: o uso das novas tecnologias no processo ensino-aprendizagem de matemática na educação básica - Oliveira, Franco Cleidson Fonseca (Universidade Federal Rural do Semi-Árido, 2021)
This work is a study on the use of computers in math classes, more precisely, the use of Excel as a teaching and learning. This constitutes a bibliographic work, but qualitatively, by expressing the need to use new technologies in the schools of basic education. Presents are then divided in to chapters, even taken separately, they forman organized whole and interconnected by means of the above. The first chapter deals with the mathematics as a science, from its inception to the present day and its meaning. The second chapter is responsible for teaching and learning of mathematics, commenting on what teaching and learning, but above all, what is teaching and learning Mathematics in Basic Education. The third chapter shows the use of new technologies in educational settings, especially considering the use of computers in mathematics classes so you can just use Excel. The fourth and final chapter presents a parallel bet ween Informatics and Mathematics, so that Excel is experienced in the classroom, which leads to the suggestion of its use in the classroom
Keywords: Matemática; Informática; Excel; Ensino e Aprendizagem; Mathematics; Computer; Excel; Teaching and Learning; CIENCIAS EXATAS E DA TERRA::MATEMATICA